Global prevalence of hepatitis C in prisoners: a comprehensive systematic review and meta-analysis - Salari, Nader; Darvishi, Niloofar; Hemmati, Mahvan; Shohaimi, Shamarina; Ghyasi, Yasaman; Ghyasi, Yasaman; Bazrafshan, Mohammad Rafi; Akbari, Hakimeh; Mohammadi, Masoud (Springer, 2022)
Hepatitis C virus (HCV), one of the most significant causes of liver inflammation, has a high annual mortality rate. The unfavorable hygiene conditions and inadequate health monitoring in many prisons increase the risk of blood-borne infections such as hepatitis C. The growing incidence of this disease among prisoners results in overspill transmission to the general population from undiagnosed prisoners that have been released. Therefore, the aim of this study was to investigate the prevalence of hepatitis C among the world's prison population. A systematic review and meta-analysis of studies on the prevalence of hepatitis C was carried out using the keywords “Prevalence”, “Hepatitis C”, and “Prisoner” in the Iranian and international databases SID, MagIran, Iran Doc, Science Direct, Scopus, PubMed, and Web of Science (WoS) from January 1990 to September 2020. After transferring the articles to the information management software EndNote and eliminating duplicate studies, the remaining studies were reviewed based on inclusion and exclusion criteria, three stages of primary and secondary evaluation, and qualitative evaluation. Comprehensive meta-analysis software and Begg and Mazumdar and I2 tests were used for data analysis and assessment of dissemination bias, and heterogeneity, respectively. Out of 93 studies (22 from Asia, 26 from Europe, seven from Africa, 29 from America, and nine from Australia) with a total sample size of 145,823 subjects, the prevalence of hepatitis C in prisoners worldwide was estimated to be 17.7% (95% confidence interval, 15-20.7%). The highest prevalence of hepatitis C on the continents included in this study was reported in prisoners incarcerated in Australia and Oceania, with 28.4% (95% CI: 21.6-36.4) in nine studies, and Europe, with 25.1% (95% CI: 19.4-31.8) in 26 studies. All studies used an ELISA test for the detection of HCV antibodies. The results showed a prevalence of HCV of 17.7% in prisoners worldwide, ranging between 10 and 30% over five continents (Asia, Europe, America, Africa, and Australia and Oceania). The highest prevalence was reported in Australia and Oceania (28.4%), indicating the need to pay more attention to this issue on the continent. It is necessary to reduce the incidence of the disease in prisons by appropriate policy-making and the development of accurate and practical programs, including the distribution of free syringes and examination, testing, and screening of prisoners.